PERAN INSTITUSI MASJID SEBAGAI PUSAT PEMBERDAYAAN SOSIAL EKONOMI MASYARAKAT (Studi di Masjid Sabilillah Malang) - Faizaturrodhiah, Nur; Pudjihardjo, M.; Manzilati, Asfi (IQTISHODUNA, 2018)
Abstract: This study aims to analyze the role of mosque institution as the center of socio-economic empowerment of the community. The study was conducted at Sabilillah Mosque which is a large national pilot mosque. The approach used is case study. The results of social empowerment research are, improving the quality of education, family assistance, business training, health services, network strengthening with mushollah. While economic empowerment among others economic empowerment through mosque cooperative, economic empowerment dhuafa through business capital and provision of production facilities, economic empowerment through provision of market pujasera. To generate other funding sources as a means to empower the community, Sabilillah Mosque organizes auditorium, cash receipts, and minimarket management cooperation.